Functional genomics analysis of the effects of co-inhibition of the malarial S-adenosylmethionine decarboxylase/ornithine decarboxylase - Louw, Abraham Izak (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2008.